The Effect of Culturally-Based Interventions on Stunting Prevention Efforts in Children Aged 0–5 Years: A Systematic Literature Review - Zubair, M. Abdul Hamid; Rekawati, Etty; Rahmadiyah, Dwi Cahya; Sari, Indah Permata (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: The high rate of stunting is closely linked to cultural influences within local communities. Therefore, health promotion intervention strategies need to be adapted to align with the cultural context of each community. Objective: This study aims to analyze culturally based interventions for preventing stunting in children aged 0–5 years. Methods: This literature review was conducted systematically using the PRISMA 2020 guidelines. Searches across five databases (ProQuest, ScienceDirect, Taylor & Francis, Scopus, and Google Scholar) yielded seven articles involving 352 participants who received culturally based stunting prevention interventions. Results: Seven articles were analyzed in depth, including three experimental studies without control groups. Five studies reported that culturally based health education interventions effectively improved knowledge, attitudes, and stunting prevention practices among caregivers of toddlers (p<0.05). The remaining two studies found that culturally grounded supplementary feeding interventions improved toddlers’ nutritional status (p<0.05). Conclusion: Culturally based interventions are effective in strengthening stunting prevention efforts for children aged 0–5 years. Integrating cultural approaches enhances community acceptance and can serve as a strategic option for governments to accelerate stunting reduction programs.